Providing supportive care to cancer patients: a study on inter-organizational relationships - Brazil, Kevin (Igitur, Utrecht Publishing & Archiving, 2008)
BACKGROUND: Supportive cancer care (SCC) has historically been provided by organizations that work independently and possess limited inter-organizational coordination. Despite the recognition that SCC services must be better coordinated, little research has been done to examine inter-organizational relationships that would enable this goal. OBJECTIVE: The purpose of this study was to describe relationships among programs that support those affected by cancer. Through this description the study objective was to identify the optimal approach to coordinating SCC in the community. METHODS: Senior administrators in programs that provided care to persons and their families living with or affected by cancer participated in a personal interview. Setting: South-central Ontario, Canada. Study population: administrators from 43 (97%) eligible programs consented to participate in the study. RESULTS: Network analysis revealed a diffuse system where centralization was greater in operational than administrative activities. A greater number of provider cliques were present at the operational level than the administrative level. Respondents identified several priorities to improve the coordination of cancer care in the community including: improving standards of care; establishing a regional coordinating body; increasing resources; and improving communication between programs. CONCLUSION: Our results point to the importance of developing a better understanding on the types of relationships that exist among service programs if effective integrated models of care are to be developed.